2019
DOI: 10.1038/s41586-019-1187-2
|View full text |Cite
|
Sign up to set email alerts
|

Hypo-osmotic-like stress underlies general cellular defects of aneuploidy

Abstract: Aneuploidy, referring to unbalanced chromosome numbers, represents a class of genetic variation associated with cancer, birth defects and eukaryotic microbes 1 – 4 . Whereas it is known that each aneuploid chromosome stoichiometry can give rise to a distinct pattern of gene expression and phenotypic profile 4 , 5 , it has remained a fundamental question as to whether there are common cellular defects ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
154
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(161 citation statements)
references
References 30 publications
5
154
2
Order By: Relevance
“…In the CAGE response, the genes that are upregulated in the ESR are downregulated, and those that are downregulated in the ESR are upregulated. The authors further found that the CAGE response bears similarity to a hypo-osmotic shock gene expression pattern, which was proposed to counter a decrease in cytoplasmic density observed in aneuploid cells (9,10).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In the CAGE response, the genes that are upregulated in the ESR are downregulated, and those that are downregulated in the ESR are upregulated. The authors further found that the CAGE response bears similarity to a hypo-osmotic shock gene expression pattern, which was proposed to counter a decrease in cytoplasmic density observed in aneuploid cells (9,10).…”
Section: Introductionmentioning
confidence: 91%
“…A recent study (9) reported the absence of the environmental stress response (ESR) in populations of yeast cells harboring different, random aneuploid karyotypes. Instead, it was reported that these heterogeneous aneuploid yeast populations exhibit the "common aneuploidy gene-expression" (CAGE) signature.…”
Section: Exponentially Growing Haploid Cells Exhibit a Transcriptionamentioning
confidence: 99%
See 3 more Smart Citations